Prohibitin modulates periodontium differentiation in mice development - Aryal, Yam Prasad; Han, Song-Yi; Rana, Bandana; Neupane, Sanjiv; Kim, Tae-Young; Pokharel, Elina; Ha, Jung-Hong; Jung, Jae-Kwang; An, Chang-Hyeon; Kim, Ji-Youn; Yamamoto, Hitoshi; Lee, Youngkyun; et al. (Frontiers in Cell and Developmental Biology, 2024)
Prohibitin (PHB) is an essential scaffold protein that modulates signaling pathways controlling cell survival, metabolism, inflammation, and bone formation. In this study, we conducted a range of experiments to examine the detailed expression pattern and function of PHB in periodontium development. We initially investigated the immunolocalization pattern of PHB alongside morphological changes in the periodontium of mice mandibles at PN5, 8, and 10. To further understand the developmental role of PHB in the formation of the alveolar bone process in mice, Phb morpholino was micro-injected into the right-side mandible at PN5, corresponding to the position where the alveolar bone process forms in relation to the lower first molar. The micro-injection with a scramble control (PF-127) and the left-side mandibles were used as control groups. At 5 days post-micro-injection, Phb knocking down showed weak immunolocalizations of runt-related transcription factor (RUNX2) and osteocalcin (OCN). In addition, knocking down Phb led to histological alterations characterized by decreased bone mass and stronger localization of PERIOSTIN in the periodontium compared to control groups. These morphological changes were confirmed through micro-CT evaluation. Additionally, we examined the expression patterns of signaling molecules following the downregulation of Phb using 24-hour in vitro cultivation of developing dental mesenchyme at E14.5. Our results indicated that the downregulation of Phb caused alterations in Bmps, Runx2, and Wnt signalings. The region-specific localization of PHB in the margin where alveolar bone forms suggests its involvement in alveolar bone formation and the differentiation of the periodontal ligament. Overall, our findings suggest that Phb plays a modulatory role in alveolar bone 3 formation by harmoniously regulating bone-forming-related signaling molecules during periodontium development.